CCD photometry in the region of NGC 6994: the remains of an old open cluster - Bassino, Lilia Patricia (2000)
We present the results of BV(RI)KC CCD photometry down to V=21 mag in the region of NGC 6994. To our knowledge, no photometry has previously been reported for this object and we find evidences that it is a poor and sparse old open cluster, with a minimum angular diameter of 9 arcmin, i.e. larger than the 3 arcmin originally assigned to it. We obtain a color excess EB-V = 0.07 ± 0.02 mag by means of the BVIC technique. Based on the theoretical isochrones from VandenBerg (1985) that are in better agreement with our data, we estimate for this cluster a distance from the Sun of 620 pc (V0 - MV = 9 ± 0.25 mag) and an age lying within the range of 2 - 3 Gyr, adopting solar metallicity. Thus, the corresponding cluster's Galactocentric distance is 8.1 kpc and is placed at about 350 pc below the Galactic plane. According to these results, NGC 6994 belongs to the old open cluster population located in the outer disk and at large distances from the Galactic plane, and must have suffered significant individual dynamical evolution, resulting in mass segregation and evaporation of low mass stars.